Pre-symptomatic development of lower motor neuron connectivity in a mouse model of severe spinal muscular atrophy. - Murray, L; Lee, S; Bäumer, D; Parson, S; Talbot, K; Gillingwater, T (2010)
The childhood motor neuron disease spinal muscular atrophy (SMA) results from reduced expression of the survival motor neuron (SMN) gene. Previous studies using in vitro model systems and lower organisms have suggested that low levels of Smn protein disrupt prenatal developmental processes in lower motor neurons, influencing neuronal outgrowth, axon branching and neuromuscular connectivity. The extent to which these developmental pathways contribute to selective vulnerability and pathology in the mammalian neuromuscular system in vivo remains unclear. Here, we have investigated the pre-symptomatic development of neuromuscular connectivity in differentially vulnerable motor neuron populations in Smn(-/-);SMN2 mice, a model of severe SMA. We show that reduced Smn levels have no detectable effect on morphological correlates of pre-symptomatic development in either vulnerable or stable motor units, indicating that abnormal pre-symptomatic developmental processes are unlikely to be a prerequisite for subsequent pathological changes to occur in vivo. Microarray analyses of spinal cord from two different severe SMA mouse models demonstrated that only minimal changes in gene expression were present in pre-symptomatic mice. In stark contrast, microarray analysis of late-symptomatic spinal cord revealed widespread changes in gene expression, implicating extracellular matrix integrity, growth factor signalling and myelination pathways in SMA pathogenesis. Taken together, these data suggest that reduced Smn levels induce SMA pathology by instigating rapidly progressive neurodegenerative pathways in lower motor neurons around the time of disease onset rather than by modulating pre-symptomatic neurodevelopmental pathways.